PENGEMBANGAN EKONOMI, SOSIAL, DAN PARIWISATA DESA KARAMATWANGI - Susetyaningsih, Adi; Hakim, Firman Nur; Anggara, Daffa Rizky; Destianti, Rahayu Giska; Putri Anggana, Syalwa Nabila; Hidayat, Rizqy Rachmat; Firdaus, Muhammad Raihan; Ikhsannudin, Adam Fadly; Wiyoga, Rangga Bisma; Ginaski, Zaki Muhamad; Muhammad Aldi Rizki; Saputra, Dimas Febrian; Zipa, Naylla Azizha; Juniarti, Sintia; Purwani, Rosdiana Putri; Sari, Putri Audya; Aidil Saepul Rohman, Agum; Kosasih, Andrean; Fadhillah, M Jamil Al; Sujiwo, Bagas; Alam, Romy Zaenul (Institut Teknologi Garut, 2025)
The development program for Karamatwangi Village, Garut Regency, was implemented to address community needs in the areas of economy, health, infrastructure, and tourism. The activities were designed using a work breakdown structure (WBS) approach, which divides the program into measurable stages ranging from planning and implementation to evaluation. The economic sector focused on issuing Business Identification Numbers (NIB), promoting the use of QRIS, and digitalizing micro-enterprises; the health sector included education on healthy homes; the infrastructure sector involved the installation of public street lighting and supporting facilities; while the tourism sector was enhanced through the management of the Tepas Papandayan agro-tourism area with a digital ticketing system. The results show an increase in the community’s capacity to manage businesses, heightened awareness of environmental health, and strengthened village tourism appeal. The application of WBS proved effective in ensuring that activities were carried out systematically, easily monitored, and capable of generating recommendations for the sustainability of community empowerment.